Strengthening Institutions and Governance in the Palm Oil Sector for Smallholder Empowerment: A Soft-Structural-Analytical Systems Model - Valentina Febi Gurning; Yance Bernat; Gusman Adiyat; Viktor Kusri (Jurnal Riset Ilmu Teknik, 2025)
This study formulates a model for strengthening the institutions of independent oil palm farmers in Kalimantan through a systemic and participatory approach. The weaknesses of independent oil palm farmers' institutions remain a major obstacle to increasing productivity, competitiveness, and the sustainability of farming businesses. This research method integrates Soft Systems Methodology (SSM), Interpretative Structural Modelling (ISM), and Analytical Hierarchy Process (AHP) to identify key elements, map structural relationships between variables, and determine institutional strengthening strategy priorities. The SSM results show that the root causes of institutional problems include low member participation, weak coordination between parties, and limited access to capital and information. The ISM analysis reveals that government support and farmers' willingness to change are the main driving elements, while professional human resource development and access to capital serve as connecting elements. Meanwhile, the AHP results show that developing partnerships among stakeholders (0.529) is the highest strategic priority, followed by improving organizational management (0.211) and enhancing training and mentoring (0.156). These findings emphasize the importance of synergy between the government, financial institutions, farmer associations, and palm oil companies in building strong, adaptive, and sustainable farmer institutions. Theoretically, this research contributes to the development of an integrated systems approach in strengthening agricultural institutions in Indonesia, particularly in the smallholder palm oil sub-sector.